Leadership Succession in Catholic Schools: Planned or Unplanned? - Canavan, fms, Kelvin (Catholic Education: A Journal of Inquiry and Practice, 2001)
The management of leadership succession at various levels of the enterprise is something every organization faces; but in recent times education researchers in the U.S., the U.K., New Zealand, and Australia have all reported an increasing difficulty in attracting principals for Catholic schools. The problem is not restricted to Catholic schools. This article details a flexible 12-phase process designed to ensure that when a vacancy occurs the organization has available people who have received some preparation for the position. A framework for the development and induction of leaders in Catholic education is provided. The strategy, developed and implemented by the author in recent years, is both practical and appropriate for use at various levels, from faculty coordinators and principals to superintendents.